CRISPR: On How it'll Change the Future - Alvina Aulia; Rael Russel Hutapea; Prawira Setya Abdima; Akhmad Ali Emawan; Ivan Sebastian Edbert (Bina Nusantara University, 2023)
Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) explain genetic illness and how people can treat it using. CRISPR, a gene editing technology, has altered what is now possible in animal modification and the development of human treatments. Technological advancements enable new enhanced plants, breakthrough concepts for human medicine, and appealing yet feasible techniques for reducing vector-borne illnesses. CRISPR is used as a diagnostic method for several critical diseases like cancer. CRISPR can detect and identify the DNA and RNA to identify the cause of the pathogen, like viruses or bacteria with high sensitivity. In this research, the researcher will explain how CRISPR will change the future, specifically for medical purposes. The researcher will do the Systematic Literature Review (SLR) to describe CRISPR. The goal considering CRISPR in the future is routinely used to edit the genetics of plant, bacterial, and even animal models for good purposes. It also nourishes and protects the human body from diseases by examining target genes in genome modification, investigating, and treating genetic disorders, infectious diseases, and immunological diseases. In CRISPR applications for hereditary illnesses, the CRISPR/Cas technology has been used for gene therapy to protect humans against sickness. Although the limitation of the technology is that still in the initial stages, CRISPR could be one of the groundbreaking methods in the future.